Review Pengaruh Jenis Material Atap terhadap Efisiensi Pemanenan Energi dengan Piezoelektrik sebagai Konverter Energi Mekanik menjadi Energi Listrik - Muhammad Fahmi Nurhidayat; Rifky; Kurnia Sandi Oktaris; Pandu Kusuma Pangestu; Reyhan Martin Firnanda; M. Ravi Cahya Firdaus (Prosiding Seminar Nasional Teknoka, 2025)
This research discusses the design of a piezoelectric raindrop energy harvesting system integrated into a building's roof surface. The primary objective of the research is to convert the kinetic energy of raindrops into electrical energy by utilizing the piezoelectric effect, while simultaneously designing efficient material and structural configurations that are resistant to dynamic loads. The methodology used refers to the VDI 2221 systematic engineering approach, encompassing requirements identification, concept design, material selection, numerical simulation, and prototype fabrication and testing. The piezoelectric materials used are PVDF and PZT, installed under a polycarbonate roof layer with a rectifier system and energy storage capacitors. Test results show that the system is capable of generating voltage and electrical power proportional to rainfall intensity, with maximum voltage distribution occurring in the central area of the piezoelectric plate. This research demonstrates the potential of utilizing raindrop energy as a renewable energy source and supports innovation in environmentally friendly smart roof designs.